Kheyti : product and business development at an agtech social enterprise - Sahay, Saumya; Sawhney, Mohanbir S. (London : Kellogg School of Management, 2017)
In early 2017, after launching its successful "Greenhouse-in-a-Box" pilot project in India with fifteen smallholder farmers, Kheyti, a non-profit agricultural technology (AgTech) social enterprise, was struggling with several decisions in developing and growing its business. Kheyti was launched in 2015 to help smallholder farmers battle poverty and income variability by providing affordable technologies bundled with services. Over eighteen months, the team had developed a low-cost and modular greenhouse product to which it added financing, inputs, training, and market linkages to create a comprehensive "full-stack" solution for small farmers. The pilot project was a success in many ways, but Saumya, Kheyti's co-founder and head of product, was concerned that it revealed shortcomings that could severely affect the viability and scalability of Kheyti's solution.Saumya had some important decisions to make. Should Kheyti redesign the product from scratch, or find other ways to reduce the cost for early adopters? Should it rely on upfront revenues from sales of the greenhouse, or consider developing an innovative financing or contract farming model? Kheyti's dwindling cash reserves meant that these decisions were urgent and critical. The path chosen now would determine whether the startup would move beyond the pilot stage and achieve its vision of serving 1 million farmers by 2025.
Originally published in Sahay, S., & Sawhney, M. (2017). Kheyti: Product and business development at an AgTech social enterprise. 5-217-253. Evanston: IL. Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kheyti -- Management; Small business -- Management; Social entrepreneurship